How do social factors relate to blunted facial affect in schizophrenia? A digital phenotyping study using ambulatory video recordings. (June 2022) - Cowan, Tovah; Strauss, Gregory P.; Raugh, Ian M.; Le, Thanh P.; Cohen, Alex S.
Abstract: Clinical interviews and laboratory-based emotional induction paradigms provide consistent evidence that facial affect is blunted in many individuals with schizophrenia. Although it is clear that blunted facial affect is not a by-product of diminished emotional experience in schizophrenia, factors contributing to blunted affect remain unclear. The current study used a combination of ambulatory video recordings that were evaluated via computerized facial affect analysis and concurrently completed ecological momentary assessment surveys to assess whether blunted affect reflects insufficient reactivity to affective or contextual factors. Specifically, whether individuals with schizophrenia require more intense affective experiences to produce expression, or whether they are less reactive to social factors (i.e. being in the presence of others, social motivation). Participants included outpatients with schizophrenia (n = 33) and healthy controls (n = 31) who completed six days of study procedures. Multilevel linear models were evaluated using both Null-Hypothesis Statistical Testing and Bayesian analyses. Individuals with schizophrenia displayed comparable expression of positive and negative emotion to controls during daily life, and no evidence was found for a different intensity of experience required for expression in either group. However, social factors differentially influenced facial expression in schizophrenia compared to controls, such that individuals with schizophrenia did not modulate their expressions based on social motivation to the same extent as controls. These findings suggest that social motivation may play an important role in determining when blunting occurs.